Pastor Gustav Olsen in polar suit. Thule, Greenland 1931 : Pastor Gustav Olsen i polardragt. Thule, Grønland 1931 - Unknown (University of Southern California Digital Library (USC.DL), 2015)
Pastor Gustav Olsen in polar suit. Thule, Greenland 1931